Does the Catholic Church Have a Mission “with” Jews or “to” Jews? - Boys, Mary C. (Studies in Christian-Jewish Relations, 2011)
Over the course of developments since Vatican II, Catholics scholars engaged in dialogue with Jews have interpreted the church's mission as one "with" Jews in furthering the Reign of God. Yet it is evident that others advocate a mission "to" Jews, that is, seek to convert Jews. This essay reviews and assesses the various theological perspectives with regard to the mission of the Catholic Church in relationship to the Jewish people.